Association of diet and physical activity with BMI among dental students in Puducherry - Radhika, B.; Vrushabhendra, H. N.; Surendar, R.; Arthi, S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Adolescence is the age where the influence of marketing world is high and choice of right food and exercise becomes hurdled. The World Health Organization alarm on increasing NCDs among adolescents ratifies the need for appropriate intervention at this age group. The objective of the study was to find out the association between diet and physical activity with body mass index (BMI) among dental students in Puducherry. Methods: A cross-sectional study was conducted in October 2016 among 85 dental students of Sri Venkateshwaraa Dental College, Puducherry. A self administered semi structured questionnaire was used to collect information about diet and physical activity. Height and weight were measured for all participants to compute BMI. Results: The mean age of the study participants was 19.32 ± 0.6 yrs. Majority of them were females (76.5%). About 33% of students had normal BMI. Junk food consumption was 91.8% and 65% had habit of skipping meals. Only 38% of the students were doing regular physical activity. A significant association between calorie and protein intake with BMI categories viz: underweight, normal, overweight and obesity was observed (p<0.001). There was a significant association (OR=18.4, 95%CI-6.1, 54.6) between excess calorie intake and BMI but not between physical activity and BMI (OR=1.2, 95% CI-0.5, 3). Conclusions: Improper dietary habits including high calorie/protein intake was associated with increased BMI among the dental students. The role of regular physical activity alone as a single factor influencing variations in BMI among the students could not be established in the study.